Pengaruh likuiditas, leverage, dan profitabilitas terhadap financial distress - Yuda Pratiwi, Elsa; Sudiyatno, Bambang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Unstable economic conditions can affect the performance of both small and large companies. Companies must implement good corporate governance in managing their companies, with this the possibility of companies experiencing financial difficulties will be smaller. This study aims to measure and analyze the effect of liquidity, leverage, profitability, and size on the financial distress of service companies listed on the Indonesia Stock Exchange (IDX) in the 2014-2020 period using the purposive sampling method. The sample criteria set by the author are 105 companies with a total of 6 years of observation. The analytical tool used in this study is logistic regression analysis. The results of this study indicate that liquidity, leverage, profitability have no significant effect on financial distress while size does not act as a control variable.